Microscopical and immunohistochemical studies on intestinal signet-ring cell and pulmonary bronchiolar-alveolar carcinoma in cat - Bambang Ponco Priosoeryanto; Ryoji Yamaguchi; Susumu Tateyama; Koudai Matsuyama (Hemera Zoa, 1992)
A rare case of signet-ring cell (SRC) carcinoma of the intestines occurring in a cat, 9,5 years old, female was described.